Correlates of problem resolution during parent-child discussions about chronic illness management. Issue 3 (2nd July 2016) - Friedrich, Elizabeth; Jawad, Abbas F.; Miller, Victoria A.
Abstract: Families impacted by pediatric chronic illness must navigate treatment regimens that can present multiple problems and decisions to be addressed on a daily basis. The extent to which parents and children are able to solve such problems is likely to have implications for health behaviors and outcomes. The aims of this study were to examine correlates of problem resolution in families of children with a chronic illness. Participants were 167 children (ages 8–16) with type 1 diabetes or cystic fibrosis and a parent. Parent-child dyads recounted a recent discussion they had related to illness management and completed questionnaires. The research team coded the discussions for topic and outcome (i.e., did the dyad come up with a plan to address the problem). The results indicated that the majority of dyads in both illness groups came up with a plan during their discussions. Lack of problem resolution during the discussion was associated with higher parent coercion, more child resistance to the regimen, and worse adherence. Parent coercion and child resistance could be the targets of interventions to enhance problem solving and improve adherence.